2023
DOI: 10.3390/ani13030342
|View full text |Cite
|
Sign up to set email alerts
|

Production of Genetically Modified Porcine Embryos via Lipofection of Zona-Pellucida-Intact Oocytes Using the CRISPR/Cas9 System

Abstract: The generation of genetically modified pigs has an important impact thanks its applications in basic research, biomedicine, and meat production. Cloning was the first technique used for this production, although easier and cheaper methods were developed, such as the microinjection, electroporation, or lipofection of oocytes and zygotes. In this study, we analyzed the production of genetically modified embryos via lipofection of zona-pellucida-intact oocytes using LipofectamineTM CRISPRMAXTM Cas9 in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Moreover, our previous study demonstrated that the removal of ZP required for lipofection-based gene editing in zygotes had no deleterious effects on embryo development Takebayashi et al, 2022). In contrast, a recent study indicates that the increased concentration in the media of the liposomes RNPs during IVF had a detrimental effect on embryo development, as the cleavage and blastocyst rates were significantly reduced (Piñeiro-Silva et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our previous study demonstrated that the removal of ZP required for lipofection-based gene editing in zygotes had no deleterious effects on embryo development Takebayashi et al, 2022). In contrast, a recent study indicates that the increased concentration in the media of the liposomes RNPs during IVF had a detrimental effect on embryo development, as the cleavage and blastocyst rates were significantly reduced (Piñeiro-Silva et al, 2023).…”
Section: Discussionmentioning
confidence: 96%